Juridic Review Concerning Implementation of Cooperative Save-Loan Credit Agreements Based on The Book of Civil Law - Ahmad Shubhan Rafie; Ilham Abbas (Manunggal Halim Jaya, 2021)
This study aims to determine the implementation of savings and loan credit agreements in cooperatives based on the law that applies holistically in Indonesia and to find out the obstacles in the process of credit agreements for savings and loans at the Mallomo Jaya Abadi Cooperative. This study uses empirical legal research methods, namely legal research that focuses on researching the legal reality in society by utilizing cooperatives in Makassar City as a research area. The results of this study indicate that the implementation of the agreement between the parties is straightforward. Cooperative members simply submit guarantees that are in accordance with the goods that have been determined by the Savings and Loans Cooperative (KSP) and are in accordance with legal norms, but there are still inhibiting factors in the process of credit agreements for savings and loans in cooperatives in the research area, namely due to professional factors and defaults in the Cooperative. Other financial institutions. As a finding of this study that was technically resolving disputes if members of the Cooperative are in default, the Management of the Mallomo Jaya Abadi Cooperative will go to the members of the cooperative and ask the problem why members of the cooperative cannot pay their loans into a family pattern that is carried out to realize the collaborative concept. This research recommends that the Mallomo Jaya Abadi Cooperative, in determining the value of the guarantee, is more careful to take into account that if the members of the Cooperative make payments in arrears for a long time, the value of the contract can still cover the principal debt and costs for the delay and it is hoped that the Cooperative should be more assertive in carrying out the contents of the agreement and take action against Cooperative members who violate the arrangement according to the law, namely gradually giving warnings in accordance with the contract, both verbal alerts and written warnings based on the principle of kinship initiated by the Cooperative.